Chronotropic, Inotropic and Dromotropic Parameters of the Heart and Oxidative Stress in Rats Receiving High Doses of Fructose: - Dianat, Mahin; Radmanesh, Esmat; Atefipour, Narges (Galen Medical Journal, 2019)
Background: Many risk factors, including nutritional ones, contribute to cardiovascular diseases (CVDs). Increased fructose consumption, for example, can lead to an increase in CVD risk factors, i.e. an increase in blood lipids and the development of insulin resistance.Â Materials and Methods: In the present study, Sprague Dawley rats were divided into two groups: Â control group (free access to tap drinking water for seven weeks), and a group that received fructose 10% in drinking water for seven weeks, (n â•8 per each group). In all groups, before starting the test period and seven weeks after it, electrocardiogram was recorded by Power lab system. Unpaired t-test and two-way ANOVA were used for data analysis. Also, oxidative stress parameters were measured.Â Results: In the group received high doses of fructose, a significant reduction (P <0.05) was observed in the PR interval (P<0.001) and a significant increase (P<0.05) in the QTc interval. However, there was no significant change in the RR interval and the voltage of the QRS complex. A significant decrease in catalase, superoxide dismutase and glutathione peroxidase (P<0.05) and a significant increase (P<0.05) in malondialdehyde and lactate dehydrogenase were observed in the group that received fructose in comparison with the control group at the end of the experiment. Conclusion: According to our results, the chance of arrhythmias in the rats receiving high doses of fructose was possibly due to the increased oxidative stress in the healthy rats. [GMJ.2019;8:e1250] Â 